Novelties in Ovine Assisted Reproductive Technologies – A Review - Dovenski, Toni; Trojacanec, Plamen; Atanasov, Branko; Nikolovski, Martin; Petkov, Vladimir; Popovska-Percinic, Florina; Dovenska, Monika; Grizelj, Juraj; Vince, Silvijo (Walter de Gruyter GmbH, 2022)
Abstract Artificial insemination (AI) as a part of assisted reproductive technologies represents the oldest and most widespread method used to accelerate genetic progress in all domestic animals. After its first implementation in ovine reproduction and almost 80 years afterward, AI is continuously used for improving the genetic merit, utilizing either fresh or short-time chilled semen. Nevertheless, regardless of the semen used for insemination, the conception rate (CR) is still lower in comparison to natural service. At least two factors are commonly thought to limit the success of the AI and reduce the CR: (1) failure of placing the semen directly into the uterus due to the specific anatomic structure of the ewe’s cervix; (2) lower viability of ram spermatozoa during cryopreservation (<30% progressively motile spermatozoa after thawing). This review elaborates on recent studies that aimed to achieve acceptable CR through the implementation of cervical or intrauterine insemination: deep intracervical, intrauterine trans-cervical, and intracornual. Several hormonal treatments (oxytocin, estrogen, or prostaglandin) were evaluated on inducing cervical dilation that facilitates insemination. A comprehensive analysis was given to the effects of several antioxidants (GSSG, GSH, and cysteine) supplemented in ram semen-freezing media. Sex-sorted ram semen fertility rate results were presented from our studies.